Vaccination In The Fight Against Covid-19 As A State Defense - Michelle Angelika S; Slamet Tri Wahyudi; Yohanes Firmansyah (Publikasi Indonesia, 2021)
Since the end of 2019 the world has been shocked by the emergence of the COVID- 19 virus, which spreads very quickly. Starting from the country of origin, namely the People's Republic of China, until in early March, Indonesia announced two positive cases of COVID-19. The COVID-19 pandemic is a threat to the Indonesian state. Various efforts have been made by the government to prevent and control the spread of this virus, ranging from restricting activities, maintaining distance, using masks, washing hands to developing vaccines. This effort is being carried out by the government as a form of state defense in fighting COVID-19. This research proves that COVID-19 is a social disaster that afflicts all walks of life, one of the methods for overcoming the Covid-19 outbreak by involving itself in the vaccination program organized by the authorities as a form of state defense.